PERSEPSI MASYARAKAT TERHADAP PELAKSANAAN PROGRAM JAMKESMAS, JAMPERSAL RUANG BERSALIN DAN RUANG PERINATOLOGI RSUD KABUPATEN BULELENG - sabrina farani (Pro Health Jurnal Ilmiah Kesehatan, 2020)
This study aimed at describing and analyzing community perception concerning the implementation of Jamkesmas program in the delivery and perinatal ward of RSUD Kabupaten Buleleng, the implementation of Jampersal program, the policy of RSUD Kabupaten Buleleng concerning with Jamkesmas and Jampersal for the under service, and the constraints faced in Jamkesmas and Jampersal programs. This study belong to the qualitative approach. The input, process, and output variables were measured by using questionnaire and interview. The results indicated that (1) the community perception on the implementation of Jamkesmas programs in the delivery and perinatal ward of RSUD Kabupaten was immediately good, (2) the implementation of Jampersal programs in the delivery and perinatal ward of RSUD Kabupaten Buleleng was immediately good, (3) the constraint was a few participantsÂ  had not yet got identity and household cards which made the requirements for participating in the program incomplete, (4) the policy of RSUD Kabupaten Buleleng, in solving the problem was to facilitate the patients in arranging forÂ  the documents in order to participate in Jamkesmas or Jampersal programs before giving care of them.